Internet addiction in young adults: The role of impulsivity and codependency - Diotaiuti, Pierluigi; Mancone, Stefania; Corrado, Stefano; De Risio, Alfredo; Cavicchiolo, Elisa; Girelli, Laura; Chirico, Andrea (Frontiers in Psychiatry, 2022)
Excessive internet use has demonstrated comorbidity with other psychological symptoms and psychiatric disorders, as well as impairments in the management of daily life, relationships and emotional stability. Recent findings in the literature have consistently supported the relationship between impulsivity and Internet addiction. The present study hypothesised that, in addition to impulsivity, a further predictor of internet addiction might be relational co-dependency, which is also associated in the literature with addiction phenomena, but mainly substance addiction. This paper investigates the role and predictive weight of impulsivity and codependency on internet addiction on a sample of young adult university students (n = 481) by using a hierarchical regression analysis. The participants were administered the UADI-2, the BIS-11 and the SFCDS. In terms of percentage distribution, 38 % of the participants were in the full dependency range, while 37.7 % demonstrated internet abuse behaviour. The results highlighted not only the confirmation of the predictive value of codependency (β = 0.275) and impulsiveness (β = 0.312), but also of the gender (β = 0.174) and age (β = 0.196) variables. Thus, male participants were more dependent, more impulsive and more co-dependent, with increasing age in the given range (18-30). The study shows that the issue is significantly present among young adults and that, as a preventive and restraining measure, there is a need not only for targeted awareness-raising programs but also for interventions to promote greater emotional control and a more balanced management of personal relationships.